Benchmarking railway vibrations – Track, vehicle, ground and building effects. (1st September 2015) - Connolly, D.P.; Kouroussis, G.; Laghrouche, O.; Ho, C.L.; Forde, M.C.
Highlights: A benchmark and review of over 230 technical railway vibration papers. Insights into holistic vibration prediction – from track to nearby buildings. Design guidelines for critical velocity based on site investigation data. Passenger comfort and railway track, ground vibration and structural vibration. Vibration effects, modelling, mitigation and future trends are synthesised. Abstract: This paper reviews, synthesises and benchmarks new understandings relating to railway vibrations. Firstly, the effect of vibrations on passenger comfort is evaluated, followed by its effect on track performance. Then ground-borne vibration is discussed along with its effect on the structural response of buildings near railway lines. There is discussion of the most suitable mathematical and numerical modelling strategies for railway vibration simulation, along with mitigation strategies. Regarding ground borne vibration, structural amplification is discussed and how vibration mitigation strategies can be implemented. There is also a focus on determining how 'critical velocity' and 'track critical velocity' are evaluated – with the aim of providing clear design guidelines related to Rayleigh wave velocity. To aid this, conventional site investigation data is reviewed and related to critical velocity calculations. The aim is to provide new thinking on how to predict critical velocity from readily available conventional site investigation data.